SOSIALISASI DAN SKRINING SEHAT JIWA PADA KEGIATAN SEKOLAH UNTUK PEMBERIAN DUKUNGAN PSIKOSOSIAL PADA REMAJA - Efi Irwansyah Pane; R Sri Rezeki; Wahyu Agustina; Nurdiana; Putri Permata Sari; Saufi Nabila (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2025)
Mental health is an inseparable part of physical health and is a major element in supporting the realization of a complete human quality of life. During adolescence, biological, psychological and social changes occur, but generally the physical maturation process occurs faster than the mental maturation process (psychosocial). Adolescents are faced with various changes that are happening in themselves and development targets that must be achieved according to their age. The purpose of this community service activity is to improve the resilience of adolescent mental health with mental health literacy with an adolescent mental health support program through communication, information and education activities. This method is in the form of psychosocial support for adolescents through socialization and mental health screening. This activity was attended by 68 students who were given questionnaires before and after the activity. The results of the analysis of the increase in the average score of student knowledge related to adolescent psychosocial support with a pre-test value of 48.28% and a post-test of 72.55%. The results of the SRQ-29 screening showed that most students experienced post-traumatic stress disorder due to natural disasters in their residential areas. The conclusion of the community service team has been carried out based on the planned stages. Suggestions for students to further improve literacy on the development of psychosocial support for adolescents.